Estimativa da Ingestão Voluntária a partir das Características de Degradação do Capim-Coastcross (Cynodon dactylon L. Pers.), sob pastejo, por Vacas em Lactação - Berchielli, Telma Teresinha [UNESP]; Soares, João Paulo Guimarães [UNESP]; Aroeira, Luiz Januário Magalhães; Furlan, Cláudia Lopes [UNESP]; Salman, Ana Karina Dias [UNESP]; Da Silveira, Roselene Nunes [UNESP]; Malheiros, Euclides Braga [UNESP] (My University, 2001)
Dry matter intake (DMI) of coastcross bermudagrass grazing by crossbred Holstein-Zebu and Zebu lactating cows was calculated using in vitro dry matter digestibility from extrusa (four esophageal fistulated cows) and fecal output estimate with mordent chromium by the non linear model. Pasture was managed in a rotational system with three days of occupation and 27 days of resting period, adopting a stocking rate of 1.6 and 3.2 cows/ha respectively during the dry and rainy season. Four different equations based on ruminal degradation were used to predict dry matter intake: DMI = -1.19 + 0.035 (a+ b) + 28.5c (I), DMI = -0.822 + 0.0748 (a+ b) + 40.7c (2), DMI = -8.286 + 0.266a + 0.102b +17.696c (3) and DMI = [%FDN na MS]* [FDN intake] / [(1-a-b)/Kp+b/(c+ kp)]/24] (4). The coast-cross DMI predicted by the equations were different from results obtained with the model (6.3 kg of dry matter/cow/day). The data achieved using the equations 1 and 2(12.2 and 12.7 kg/cow/day respectively) were similar and superior from results obtained by equation 4 (7.8 kg/ cow/day). Those values overestimated the results obtained using mordent chromium. The data obtained by equation 3 (5.5 kg/cow/day) was lower than those determined by equations and underestimated the DMI calculated with external marker. The prediction of dry matter intake from cows grazing tropical forages using equations based in ruminai degradation parameters constitutes an important potential for those evaluations, but it should be still studied before being employed in practice.
Prediction of Dry Matter Intake Based on Ruminal Degradation from Milking Cows Grazing Coastcross Bermudagrass
Keywords: Degradability; Intake; Mordanted chromium; Prediction equations; Tropical forages